So assuming that x and y are the same value in both equations we can make the first equation negative (multiply the whole thing by -1) and get
-15x+12y=-13 we multiply it by 2 and get -30x+24y=-26 we add this to the second equation (30x+9y=4)+(-30x+24y=-26) 30x-30x+24y+9y=-22 or 33y=-22 divide both sides by 11 3y=-2 divide both sides by 3 y=-2/3
we subtitute it into the first equation 15x-12(-2/3)=13 15x-(-24/3)=13 15x+8=13 subtract 8 from both sides 15x=5 divide both sides by 5 3x=1 divide both sides by 3 x=1/3